Effect of peroxydisulfate on the degradation of phenol under dielectric barrier discharge plasma treatment - Wang, Xiaojing; Zhang, Guangshan; Liu, Xiaomeng; Hu, Limin; Wang, Qiao; Wang, Peng (Chemosphere (Oxford), 2019)
The activation of peroxydisulfate (PDS) by gas/liquid dielectric barrier discharge (DBD) plasma in a flat plate configuration was assessed through phenol removal. The results indicated that PDS addition exhibited a significantly promoting effect on phenol removal and mineralization. In the reaction lacking PDS, phenol in aqueous solution was removed from the initial 10 mg L−1 to 4.75 mg L−1 (by 52.5%), whereas the addition of 1770 mg L−1 PDS increased the overall removal to 78.7%, as indicated by a one-fold increase in the pseudo-first-order kinetic constant. In addition, the corresponding total organic carbon (TOC) removal was increased from 27.5% to 48.4%. Furthermore, an increased input voltage was favourable for increases in phenol removal, the kinetic constant and PDS utilization, which were also influenced by the PDS dose, initial solution pH and water matrix. In addition, through the analysis of radical quenching experiments, the enhancement could be mainly attributed to the production of SO4•- and •OH by PDS activation by discharge plasma. The DBD system coupled with PDS exhibited a high removal efficiency for phenol, and thus, the overall findings could provide new insight into wastewater treatment. [Display omitted] •Addition of PDS in discharge plasma can improve phenol degradation and TOC removal.•Enhanced phenol removal was attributed to increment of •OH and SO4•-.•Phenol removal was simultaneously attributed to •OH, SO4•- and other chemical and physical effects.•The activation of PDS by UV generated with discharge plasma likely occurred.